Synthetic Approach to Fused Azasultams with 1,2,4-Thiadiazepine Framework - Hys, Vasyl Y.; Milokhov, Demyd S.; Volovenko, Olesya B.; Konovalova, Irina S.; Shishkina, Svitlana V.; Volovenko, Yulian M. (Synthesis, 2020)
Synthetic approach to fused azasultams with 1,2,4-thiadiazepine framework via base promoted protocols has been developed. 1H-Azole-2-carboxylates and N-(chloromethyl)-N-methylmethanesulfonamide were used as ambiphilic building blocks in the one-pot and two-step reaction sequences. Chemical behavior of the obtained azasultams in reactions with amines, hydrazine, DMFDMA, and NaBH4 was investigated. An enamino ketone derived from an azasultam was exploited in the synthesis of new pyrazole and pyrimidine heterocycles.
Keywords: sulfonamides; sultams; thiadiazepine; pyrrole-2-carboxylate; indole-2-carboxylate; cyclization; sulfa-Dieckmann condensation; supercritical fluid chromatography